Patent ductus arteriosus in preterm infants born at 23–24 weeks' gestation: Should we pay more attention?. (August 2019) - Dani, Carlo; Mosca, Fabio; Cresi, Francesco; Lago, Paola; Lista, Gianluca; Laforgia, Nicola; Del Vecchio, Antonello; Corvaglia, Luigi; Paolillo, Piermichele; Trevisanuto, Daniele; Capasso, Letizia; Fanos, Vassilios; et al.
Abstract: Background: Infants born at 23–24 weeks' gestation have the highest risk of developing a hemodynamically significant patent ductus arteriosus (hsPDA), that is refractory to pharmacological closure requiring surgical ligation. Thus, these patients might have the greatest benefits from hsPDA closure, although previous studies on PDA closure were not focused on this population. Aim: To compare the occurrence of hsPDA, failure rate of the first course of ibuprofen in closing hsPDA, and need of surgical closure in infants born at 23 +0 –24 +6 weeks' gestation to those in infants born at 25 +0 –28 +6 weeks' gestation. Study design: This is a retrospective multicenter study including infants born at 23 +0 –28 +6 weeks of gestation admitted to the neonatal care units from January 2013 to December 2017. All infants underwent echocardiographical assessment for hsPDA diagnosis and eventually pharmacological treatment, and surgical closure. Results: We studied a total of 842 infants of which 562 (67%) developed a PDA. Among those with PDA, 511 (91%) received a pharmacological treatment for a hsPDA. We found that a hsPDA occurred in 70% (106/151) of infants born at 23–24 weeks and in 59% (405/691) of infants born at 25–28 weeks of gestation (P < 0.001). Failure of closure with the first-treatment cycle (69 vs. 40%; P < 0.001) and need of surgical closure (19 vs 10%) were more frequent (P < 0.011) in infants born at 23–24 than 25–28 gestational weeks. Paracetamol vs. ibuprofen treatment and gestational age of 23–24 versus 25–28 weeks increased closure failure, while less severe RDS and maternal clinical chorioamnionitis decreased it. Conclusions: Among extremely preterm infants, infants born at 23–24 weeks of gestation have the highest risk of developing a hsPDA refractory to pharmacological treatment requiring surgical closure. Our findings support the need of individualized more careful strategies for hsPDA management in this special population. Highlights: Hemodynamically significant patent ductus arteriosus is more frequent in infants born at 23-24 weeks than in infants born at 25-28 weeks of gestation. Pharmacological closure failure was double in infants born at 23-24 weeks than in infants born at 25-28 weeks of gestation. Our findings support the need of individualized strategies for hsPDA management in infants born at 23-24 weeks of gestation.